2011
DOI: 10.1158/1078-0432.ccr-10-2523
|View full text |Cite
|
Sign up to set email alerts
|

Human Prostate Cancer Harbors the Stem Cell Properties of Bone Marrow Mesenchymal Stem Cells

Abstract: Purpose Prostate tumor cells frequently show the features of osteoblasts, which are differentiated from bone marrow mesenchymal stem cells. We examined human prostate cancer cell lines and clinical prostate cancer specimens for additional bone marrow mesenchymal stem cell properties. Experimental Design Prostate cancer cell lines were induced for osteoblastogenic and adipogenic differentiation, detected by standard staining methods and confirmed by lineage-specific marker expression. Abnormal expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 41 publications
0
52
2
Order By: Relevance
“…One study demonstrated that prostate cancer cell lines had the ability to differentiate into osteoblasts and brown adipose. The ability of primary prostate tumor cells to differentiate was not assessed (55). A second study in ovarian cancer suggested that primary CD133 + EpCAM + CD44 + ovarian CSCs, after passage in mice, could produce mesenchymal cells in vitro (56).…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that prostate cancer cell lines had the ability to differentiate into osteoblasts and brown adipose. The ability of primary prostate tumor cells to differentiate was not assessed (55). A second study in ovarian cancer suggested that primary CD133 + EpCAM + CD44 + ovarian CSCs, after passage in mice, could produce mesenchymal cells in vitro (56).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the differentiation potential of prostate cancer cells to assume an adipocyte lineage phenotype was revealed. 27 Human prostate cancer cell lines PC3 and DU145 reversibly differentiate into an adipocyte-like phenotype in vitro under adipogenic induction conditions, leading to growth arrest and apoptosis. 27 Similarly, human prostate cancer bone metastatic tissue microarray (TMA) samples exhibit a brown fatspecific marker, UCP1, suggesting that prostate cancer cells may also differentiate into an adipocyte phenotype in vivo.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…27 Human prostate cancer cell lines PC3 and DU145 reversibly differentiate into an adipocyte-like phenotype in vitro under adipogenic induction conditions, leading to growth arrest and apoptosis. 27 Similarly, human prostate cancer bone metastatic tissue microarray (TMA) samples exhibit a brown fatspecific marker, UCP1, suggesting that prostate cancer cells may also differentiate into an adipocyte phenotype in vivo. 27 As the differentiation potential of prostate cancer is likened to that of MSCs, 27 it is also possible that disseminated prostate cancer acquires an MSC-like phenotype to colonize the bone marrow.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The upregulation of β2-microglobulin, an immune regulator protein, can induce EMT, promote osteomimicry, and lead to bone metastasis in mouse models of prostate and other cancers [31]. Furthermore, PC cell lines can be forced to differentiate into osteoblast-like cells or adipose cells [32], suggesting that PC cells have the inherent capability to change phenotypes. Additional studies have established that PC cells produce soluble factors that lead to the expression of osteoblast-specific genes [33].…”
Section: Preclinical Evidence Of Ep In Pcmentioning
confidence: 99%